Changes in 18F-FDG-PET/CT tumor metabolism are not consistent with pathologic complete response in hormone-positive breast cancer - DEDE, FUAT; KAYA, HANDAN; UĞURLU, MUSTAFA ÜMİT (My University, 2017)
© 2017 Zerbinis Publications. All rights reserved.Purpose: Current evaluation of response to neoadjuvant chemotherapy (NAC) shows that it could achieve pathological complete response (pCR). The purpose of this study was to assess the consistency of maximum uptake values (SUVmax) changes and pCR in hormone-positive locally advanced breast cancer (LABC). Methods: Ninety hormone-positive LABC patients treated at Marmara University Medical Oncology Clinic, Istanbul, Turkey, between 2009 and 2015 were retrospectively studied. All eligible patients (n=51) received NAC (4-8 cycles) and were evaluated for pCR. 18F-fluorodeoxyglucose positron emission tomography/ computed tomography (18F-FDG-PET/CT) scan was performed before and after the completion of NAC. The relative changes of SUVmax both in the primary tumor and the axilla were assessed for consistency with pCR. Results: The patient median age was 46 years (range 26-76). The patients 13.7% achieved pCR. Values of >50% (n=40) and 75% SUVmax changes could achieve pCR of 20%. Interestingly, most patients with complete metabolic response did not achieve pCR (81%). The difference of the Ki67 levels before and after NAC, tumor localization, HER-2 positivity, menopausal status, grade of differentiation, lymphovascular and perineural invasion were not associated with pCR. Conclusion: SUVmax changes in later cycles of NAC as commonly practised in oncology clinics were not consistent with pCR (p=1.0). Complete metabolic response may not be associated with pCR in hormone-positive LABC. However, almost 80% of patients had >50% decrease in SUVmax and may still have a chance for conservative surgery and less postoperative morbidity. Therefore, 18F-FDG-PET/CT may still have a role to evaluate the tumor response with a need of larger studies and analysis for cost-effectiveness.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Onkoloji; Nükleer Tıp; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Hematology; Oncology; Nuclear medicine; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Moleküler Biyoloji ve Genetik; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; HEMATOLOJİ; ONKOLOJİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; HEMATOLOGY; ONCOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Radyoloji, Nükleer Tıp ve Görüntüleme; Kanser Araştırmaları; Radiology, Nuclear Medicine and Imaging; Cancer Research; 18F-FDG-PET/CT; Hormone-positive; Locally advanced breast cancer; Neoadjuvant chemotherapy; Pathologic complete response; 18F-FDG-PET/CT; hormone-positive; locally advanced breast cancer; neoadjuvant chemotherapy; pathologic complete response